Contact hypersensitivity to nickel in patients with atopic dermatitis - Michał Rożalski; Leszek Blicharz; Zbigniew Samochocki (Termedia Publishing House, 2017)
Atopic dermatitis is a chronic, recurrent inflammatory dermatosis with a complex and not fully explained pathogenesis. Recent years' research points to a significant percentage of patients with atopic eczema in whom hapten patch test results are positive, especially with respect to nickel. These observations undermine suggestions that contact allergy (type IV hypersensitivity) is rare in this group due to the dominance of the Th2-type cellular response characteristic for type I allergic reactions. In this review we aimed to systematize current knowledge regarding the pathomechanisms of contact hypersensitivity to nickel in patients with atopic dermatitis and the potential influence of this hapten on the clinical course of the disease.